2005
DOI: 10.2337/diacare.28.3.694
|View full text |Cite
|
Sign up to set email alerts
|

Can Adoption of Regular Exercise Later in Life Prevent Metabolic Risk for Cardiovascular Disease?

Abstract: OBJECTIVE -To determine the impact of chronic exercise training initiated later in life upon development of metabolic markers of cardiovascular disease risk.RESEARCH DESIGN AND METHODS -Two inception cohorts of previously sedentary healthy adults aged 55-75 years at baseline (1989), one initiating regular supervised physical exercise training and the other a geographical similar sedentary control, were assessed for anthropometric, biochemical, and clinical markers of the metabolic syndrome and comorbidity over… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
40
0
1

Year Published

2005
2005
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(42 citation statements)
references
References 49 publications
1
40
0
1
Order By: Relevance
“…These data are the first to demonstrate long-term effeets of the health authorities' guidelines for physieal aetivity (1) in relation to cardiorespiratory fitness. The observed differenee in V02peak IS Sufficiently large, on the basis of other epidemiological studies, to expect differenees in fiiture cardiovascular health, morbidity, and premature mortality rates (5,19,21). The highest level of VO2peak was reeorded among those who reported a high level of physieal activity in both surveys, and the poorest level of V02peak was reeorded among partieipants who were inaetive at both oecasions.…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…These data are the first to demonstrate long-term effeets of the health authorities' guidelines for physieal aetivity (1) in relation to cardiorespiratory fitness. The observed differenee in V02peak IS Sufficiently large, on the basis of other epidemiological studies, to expect differenees in fiiture cardiovascular health, morbidity, and premature mortality rates (5,19,21). The highest level of VO2peak was reeorded among those who reported a high level of physieal activity in both surveys, and the poorest level of V02peak was reeorded among partieipants who were inaetive at both oecasions.…”
Section: Discussionmentioning
confidence: 74%
“…Even small differences in V02peak may prediet substantial differenees in cardiovascular health, as indicated by differenees in risk factor levels (5,21) and also by differences in cardiovascular and all-cause mortality (9,19).…”
mentioning
confidence: 99%
“…Regular exercise leads to increased exercise capacity, decreased morbidity and improved HRQOL [4,[19][20][21]. It has been postulated that exercise decreases cardiovascular risk through its beneficial effects on blood pressure [22,23], triglycerides and high-density lipoprotein cholesterol [24,25], insulin resistance [26,27] and glycemic control [12].…”
Section: Introductionmentioning
confidence: 99%
“…The beneficial effect of aerobic physical activity on CV risk factors has been reported even in the elderly. [2][3][4][5][6] Cross-sectional studies have shown that physical activity is associated with lower values of pulse wave velocity carotid-femoral (PWVcf), a surrogate marker of subclinical vascular damage. [7][8][9] To date, only a few studies have evaluated the effect of physical activity on PWVcf in the elderly.…”
mentioning
confidence: 99%